Selection, substantiation and description of indicators of soil biodiversity - Писаренко, П. В.; Тараненко, С. В.; Тараненко, А. О. (Scientific Progress & Innovations, 2013)
Necessity and importance of improvement of land resources monitoring system, in particular application of soil biodiversity indicators were grounded. List of possible soil biodiversity indicators for assessment of soil biodiversity and soil function was proposed. The methods which are used or can be used for research soil biodiversity were analyzed. The main indicators for monitoring soil biodiversity which characterize research object were selected. Substantiation and description of soil biodiversity indicators were realized.